Equilibrium, kinetic and thermodynamic biosorption studies of Hg(II) on red algal biomass of Porphyridium cruentum. Issue 4 (1st October 2016) - Zaib, Maria; Athar, M. Makshoof; Saeed, Asma; Farooq, Umar; Salman, M.; Makshoof, M. Nouman
ABSTRACT: Among a variety of microbial materials employed for biosorption, algae have added advantages of non-toxic and autotrophic nature. In this study, biosorption of Hg(II) was studied with red algal biomass of Porphyridium cruentum. The parameters affecting biosorption such as dosage of biosorbent, pH, contact time, initial metal concentration, temperature and effect of foreign metal cations in binary system were evaluated. Kinetic data were described with the help of pseudo-first-order and pseudo-second-order kinetic models. Langmuir, Freundlich, Temkin and Dubinin–Radushkevich isotherm models were applied to adsorption equilibrium data. According to the results, the maximum removal capacity ( q max ) was 2.62 mg/g observed at pH 7 with 0.25 g/L of biosorbent dosage for Hg(II) solution containing 10 mg/L of metal ions. The Langmuir isotherm model fits best to the adsorption data while the kinetic data followed the pseudo-second-order model. Thermodynamics studies showed that the biosorption process of Hg(II) on P. cruentum was exothermic in nature. GRAPHICAL ABSTRACT: